2016
DOI: 10.1111/1365-2435.12734
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation rates and sources of external nitrogen in decaying wood in a Norway spruce dominated forest

Abstract: Summary Microbial respiration in dead wood contributes substantially to the long‐lived forest carbon (C) pool and has a significant role in the forest nitrogen (N) cycle. Wood N content has been found to increase during the decay process; however, temporal dynamics and the sources of this external N remain unclear. To examine N dynamics at various stages of decomposition, we combined high variety of analytical methods on Norway spruce logs, including wood δ15N, N%, 14C‐dating, fungal composition and N2 fixat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 68 publications
3
64
0
Order By: Relevance
“…A conversion factor from acetylene reduction to N fixation of 4 was used (Brunner & Kimmins, ). In the present study the N 2 fixation data (Rinne et al, ) is for the first time compared with respiration rate, nifH copy number and fungal community of Lapinjärvi deadwood, and used to calculate the AE of the N 2 fixation rate for the different decay classes. The density, N content and moisture of deadwood used in the present study (Table ) are from Rinne et al ().…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A conversion factor from acetylene reduction to N fixation of 4 was used (Brunner & Kimmins, ). In the present study the N 2 fixation data (Rinne et al, ) is for the first time compared with respiration rate, nifH copy number and fungal community of Lapinjärvi deadwood, and used to calculate the AE of the N 2 fixation rate for the different decay classes. The density, N content and moisture of deadwood used in the present study (Table ) are from Rinne et al ().…”
Section: Methodsmentioning
confidence: 99%
“…In addition, bacteria are considered to play a minor role in wood decomposition (Clausen, ), but recent studies have proven early hypothesis (Cowling & Merrill, ) that e.g. N 2 fixing bacteria may have a remarkable contribution on N availability in the decomposing wood (Rinne et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both angiosperm and conifer deadwoods have very high C:N ratios (377 in Fagus sylvatica , 630 in Picea abies ), thus microbial extraction or utilization of N from deadwood ought to be very difficult (Hoppe et al ., ). Although the C:N ratio decreases over time due to the relative accumulation of N (Rinne et al ., ), at the late decomposition stage it still remains very high (i.e., 194 in F. sylvatica and 423 in P. abies ) compared with other substrates such as soils (ranging from 9 in Greyzems to 26 in Histosols) or leaf‐litter [ranging from 54 ± 38 (mean ± SD) in tropical regions to 79 ± 30 in the Mediterranean] (Batjes, ; Aerts, ; Hoppe et al ., ). In addition, considering that C:N ratios of fungal mycelia are low (i.e., 9–20) (Wallander et al ., ; Brabcová et al ., ) and that production of wood degradation enzyme requires high amount of N, this would mean high demand of N for wood‐inhabiting fungi (WIF) is expected (Hoppe et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Hoppe et al (2014) found a stronger positive correlation between fungal fructification and nifH diversity during the intermediate stage of decay of P. abies and Fagus sylvatica logs. Another plausible explanation could be related to the moisture content, because it is known to be one of the limiting factors of the biological nitrogen fixation (Rinne et al 2017). In fact, a decrease in wood moisture level was found at the end of the monitoring period in our study.…”
Section: Discussionmentioning
confidence: 45%